The effect of teaching props on the mathematical problem-solving skills: A meta-analysis study - Widodo, Sri Adi; Sari, Yuyun Novita; Chiphambo, Shakespear Maliketi; Fitriani, Nelly; Sulistyowati, Fitria; Murtafiah, Wasilatul; Pratama, Deri Fadly (IKIP Siliwangi and I-MES, 2025)
Researchers have widely researched the effects of teaching props, and most concluded that, statistically, there is an effect on problem-solving ability. However, how significant is the effect on problem-solving ability, and whether their research results are parallel to other research they have yet to do? So, the reliability of research related to teaching props still needs to be considered. This research aims to analyze the results that examine teaching props on problem-solving abilities. The method used in this research is meta-analysis. This research was carried out through meta-analysis stages, namely determining inclusion criteria, collecting data and coding variables, statistical analysis by determining the effect size, and making conclusions from the data obtained. Data collection was carried out by collecting data from research conducted from 2018 to 2023 on the Google Scholar database. This data collection obtained twenty-six (26) studies that met the inclusion criteria for extraction from research and development, experimental, and quasi-experimental. Effect size measures the effect of teaching props on students' problem-solving abilities. Based on these calculations, an effect size value of 2.449. This research indicates a significant and positive influence between teaching props and students' problem-solving skills, especially in mathematical learning. Therefore, it is necessary to develop teaching props to improve mathematical problem-solving skills.